Usability and User Friendliness Estimation of Business German Course on Moodle Platform - Zaitseva, N. (My University, 2016)
Тhe research is devoted to estimation of usability and user friendliness of Business German course on Moodle platform on basis of questionnaire among engineering Master’s program students.
Keywords: e-Learning platform; user friendliness; distance learning course materials; Business German course